Development of interactive multimedia based on adobe flash integrated with character values on the respiratory system materials - Hudson Sidabutar; Riscal Boni Tamaro Sitorus (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the feasibility of interactive multimedia learning integrated with character values developed using  Adobe Flash CS 6 Software on the respiratory system material in humans based on the responses of material experts, media experts, field teachers, and students. This study uses a 4-D model of instructional development design, including the define, design, develop, and disseminate stages, limited to the limited deployment stage to see the students' classical learning completeness, namely 36 students. class XI MIA 1 SMA Negeri 1 Sipoholon Academic Year 2021/2022. The results showed that the interactive multimedia learning developed was suitable for use in learning the human respiratory system material because it met the eligibility criteria with an average score of 4.4 from material experts included in the very good criteria, an average score of 4.3 from media experts who included in the very good criteria, the average score of 4.7 from the subject teachers included in the very good criteria, and the average score for each test 4.5 from the students included in the very good criteria.